PENGARUH INTELLECTUAL CAPITAL TERHADAP PROFITABILITAS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Marwah Astuti; Sultan sarda; Muchriana Muchran (Jurnal Ilmu Manajemen Profitability, 2019)
MARWAH ASTUTI, 2018. Effect of Intellectual Capital on Profitability in Manufacturing Companies listed on the Indonesia Stock Exchange, Thesis Management Study Program, Faculty of Economics and Business, University of Muhammadiyah Makassar. This study aims to determine the effect of Intellectual Capital on Profitability in manufacturing companies listed on the Indonesia Stock Exchange for the period 2014-2016. The population of this study is a manufacturing company that is consistently listed on the Indonesia Stock Exchange, amounting to 155 companies. The sampling technique used was purposive sampling technique. Based on the predetermined criteria obtained a sample of 54 companies. The type of data used is secondary data taken by the documentation method by accessing the site idx.co.id, Sahamok.com, and the official website of each company. The data analysis technique used is descriptive statistical analysis and simple linear regression analysis using SPSS 23. The results of the study show that there is a positive and significant effect of Intellectual Capital on Profitability, with a determinant coefficient (R2) of 0.526 or 52.6%, t count 13.317 t-table 1.65443.